FLICKER-NOISE SPECTROSCOPY: A NEW APPROACH TO INVESTIGATE THE TIME DYNAMICS OF GEOELECTRICAL SIGNALS MEASURED IN SEISMIC AREAS - Telesca L.; Lapenna V.; Timashev S.; Vstovsky G.; Martinelli G. (My University, 2004)
The Flicker-Noise Spectroscopy (FNS) is an innovative method of extracting quantitative dynamical information from time series. The method represents the signal as sequences of irregularities (spikes, jumps, discontinuities of derivatives), derived on the basis of power spectra and structural functions of different orders. By means of this method we investigated one-year hourly geoelectrical data measured during 2002 in the station Giuliano, southern Italy, one of the most seismically active areas of Mediterranean region. The analysis performed seems to reveal the potential of the FNS to identify seismic precursors.